Impact of body weight on mycophenolic acid population pharmacokinetics in paediatric lupus nephritis: a pharmacogenomic integration study - Lu Zhang; Chen Ye; Yifan Zheng; Xiaoyun Jiang; Pan Chen; Kejing Tang; Baojing Liu; Lizhi Chen (Lupus Science and Medicine, 2025)
Background Mycophenolic acid (MPA) is recommended for the treatment of lupus nephritis (LN). However, the high pharmacokinetic (PK) variability of MPA contributes to its suboptimal efficacy and an increased incidence of adverse reactions. Rare data reported the impacts of genetic and clinical characteristics on MPA clearance in the paediatric patients with LN.Methods Paediatric patients with LN receiving mycophenolate mofetil (MMF) were prospectively enrolled. MPA PK parameters were calculated on reaching steady state (defined as at least 7 days), based on plasma concentrations measured before and after administration at intervals of 0.5, 1.5, 2.5, 4, 6, 9 and 12 hours post-MMF treatment. Genetic variants associated with the MPA PK process were identified. The population PKs (PPKs) model was constructed using Phoenix NLME software and validated internally as well as externally.Results A total of 51 patients were included in the study, resulting in the acquisition of 146 area under the concentration-time curve (AUC) values. PK analysis revealed that the mean AUC value was 31.05 μg×hour/mL. The mean clearance value was 11.10 L/hour. We screened 29 single nucleotide polymorphisms across 13 candidate genes and identified that eight genetic variants within the UGT1A9, ABCC2 and CES1 genes significantly impacted the AUC of MPA. Furthermore, our data were adequately represented by a two-compartment model incorporating lag time and linear elimination kinetics. However, when combined with clinical variables, only body weight emerged as a critical covariate significantly associated with MPA peripheral volume of distribution. External validation involving nine patients demonstrated strong predictive performance.Conclusion Body weight emerges as the primary covariate over pharmacogenetic variants in PPK modelling of MPA in paediatric LN. We suggest that an individualised initial dose and adjustment based on body weight can be given in the paediatric population.